Christianity Amidst Apartheid - Prozesky, Martin. author. aut Link
X, 244 p.
Keywords: This book contains chapters by 14 prominent figures offering information on key issues concerning the Christian faith in South Africa. Three quarters of South Africans regard themselves as Christians. The story of the gospel of love and its interplay with politics is the theme pursued here.